2009
DOI: 10.1093/carcin/bgp008
|View full text |Cite
|
Sign up to set email alerts
|

Death receptor pathways mediate targeted and non-targeted effects of ionizing radiations in breast cancer cells

Abstract: Delayed cell death by mitotic catastrophe is a frequent mode of solid tumor cell death after γ-irradiation, a widely used treatment of cancer. Whereas the mechanisms that underlie the early γ-irradiation-induced cell death are well documented, those that drive the delayed cell death are largely unknown. Here we show that the Fas, tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) and tumor necrosis factor (TNF)-α death receptor pathways mediate the delayed cell death observed after γ-irradiation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 38 publications
2
48
0
2
Order By: Relevance
“…Fas ligand (FasL) interacts with its receptor Fas playing key role in apoptotic cell death. It have been reported that the Fas/FasL pathway is upregulation after ionizing radiation and has been linked with ionizing radiation-induced cell death [34-36]. Heinzelmann and colleagues found that if Fas-or FasL-deficiency, there was no characteristic pathological change of radiation-induced pneumonitis [37].…”
Section: Discussionmentioning
confidence: 99%
“…Fas ligand (FasL) interacts with its receptor Fas playing key role in apoptotic cell death. It have been reported that the Fas/FasL pathway is upregulation after ionizing radiation and has been linked with ionizing radiation-induced cell death [34-36]. Heinzelmann and colleagues found that if Fas-or FasL-deficiency, there was no characteristic pathological change of radiation-induced pneumonitis [37].…”
Section: Discussionmentioning
confidence: 99%
“…Bystander signals may be transferred to surrounding cells either by gap junctional intercellular communication or by the production of soluble extracellular factors released from irradiated cells. Soluble signaling factors such as reactive oxygen species (ROS) (8)(9)(10)(11)(12), nitric oxide (NO) (12)(13)(14), secondary messengers like calcium (4,(8)(9)(10), cytokines such as interleukins (15)(16)(17), TGFb (18,19), TNFa and TRAIL (20,21) have been found to play a major role in radiation-induced bystander effects. A new mechanism for communication by soluble factors could be by intercellular communication by exosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Bystander effects have been shown to be mediated by a variety of signalling factors including reactive oxygen species (ROS) Wu et al 1999; Azzam et al 2002;Lyng et al 2006;Harada et al 2008), nitric oxide (NO) (Matsumoto et al 2001;Shao et al 2002;Harada et al 2008), second messengers like calcium (Lyng et al 2000(Lyng et al , 2002Lyng et al 2006;Shao et al 2006), cytokines such as transforming growth factor beta (TGFβ) (Iyer et al 2000;Shao et al 2008) and interleukins (Osterreicher et al 2003;Facoetti et al 2006;Facoetti et al 2009) and tumour necrosis factor alpha (TNF-α) and tumor necrosis (TNF)-related apoptosis-inducing ligand (TRAIL) death inducing pathways (Shareef et al 2007;Luce et al 2009). In addition, cyclooxygenase-2 (COX-2) (Zhou et al 2005;Hei et al 2008), Nuclear Factor KappaB (NFkB) (Azzam et al 2002;Zhou et al 2008) and mitogen-activated protein (MAP) kinase (Azzam et al 2002;Zhou et al 2005;Lyng et al 2006) signalling have all been shown to be involved in bystander responses.…”
mentioning
confidence: 99%